The Necessity for Information Space Mapping for Information Retrieval on the Semantic Web - Gregory B. Newby (Information Research: An International Electronic Journal, 2002)
The Semantic Web offers exciting possibilities for information retrieval (IR). In IR, we would like systems that go beyond simply matching words in documents and queries, and instead match based on topic, data type, relations among data, and many other qualities. The Semantic Web, through fuzzy matching of information spaces from different sources, will provide for much more specific information seeking than current Web-based search engines or other IR systems. In order to succeed, however, it is necessary to map between the differing schema, metadata standards, namespaces and so forth used by documents on the Semantic Web. This information space mapping may be accomplished by a simple match or table lookup when document sets come from similar or otherwise well-defined domains. When the match is less precise, sets of rules or algorithms may be employed to map between information spaces. When schema or metadata are inconsistent, though, we are left with a similar data environment as the modern Web, and must rely on the context of the documents themselves to determine the mapping between information spaces.